MENINGKATKAN KECERDASAN INTERPERSONAL PADA ANAK USIA 4-5 TAHUN MELALUI MODEL PEMBELAJARANÂ REGGIO EMILIA - SN, Neneng Yeni; Zahro, Ifat Fatimah (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2020)
Interpersonal intelligence is important for life, if the interpersonal intelligence of children is good then the child will easily socialize. Early research findings show that the behavior of children aged 4-5 years wants to win alone, playing does not want to take turns and does not want cooperation with friends. The purpose of this study is to examine and find out about the application of learning in the Reggio Emilia to improve the interpersonal intelligence of children aged 4-5 years. This research method, class action research (Classroom action research) with subjects aged 4-5 years consisted of 12 male students and 15 female students in KOBER PAUD Al Hidayah. Researcher data collection techniques through observation and documentation with Kemmis and Mc Taggart models are preliminary observations of research, then enter cycle 1 including planning, action, observation, and reflection. After that the data analysis is made using data reduction to focus on the rough field data, then a data display is made where the data is compiled and then conclusions are drawn so that researchers can explain important data as the end of the study. From the results of the study obtained data on children who began to develop 25.9%, for children who develop according to expectations 37.04% and children who develop very well there is 37.04% so based on the results of research and assessment of classroom teachers that by applying the learning Reggio  Emilia can improve children's interpersonal intelligence because the learning of the region of Emilia is learning through project methods that can indirectly stimulate children to work together.Kecerdasan  interpersonal  penting untuk kehidupan, jika kecerdasan  interpersonal anak baik  maka anak  akan  mudah  bersosialisasi. Temuan penelitian awal bahwa  perilaku anak usia 4-5 tahun  ingin menang sendiri,  bermain tidak mau bergiliran, dan tidak mau kerjasama dengan temannya. Tujuan penelitian ini untuk menelaah dan  mengetahui tentang  penerapan pembelajaran  reggio emilia  untuk meningkatkan  kecerdasan  interpersonal  anak usia 4-5 tahun. Metode penelitian ini,  penelitian tindakan kelas (Classroom action research) dengan subyeknya anak  usia 4-5 tahun  terdiri dari  siswa laki laki 12 orang  dan perempuan  15 orang di PAUD KOBER Al Hidayah. Teknik pengumpulan data   peneliti   melalui observasi dan dokumentasi  dengan  model Kemmis dan MC Taggart yakni observasi awal pra penelitian,kemudian masuk siklus 1 diantaranya: perencanaan, tindakan, observasi dan  refleksi. Setelah itu dibuat analisis data dengan cara reduksi data untuk memusatkan perhatian pada data lapangan yang bersifat data kasar, kemudian  dibuat display data dimana data tersebut disusun lalu ditarik kesimpulan sehingga peneliti bisa menjelaskan  data data penting sebagai akhir penelitian.  Dari hasil penelitian diperoleh  data anak yang mulai berkembang 25,9%, untuk anak yang berkembang sesuai harapan 37,04% dan anak yang berkembang sangat baik ada 37,04% jadi berdasarkan  dari hasil penelitian dan asesmen guru kelas  bahwa dengan menerapkan  pembelajaran  reggio emilia dapat meningkatkan kecerdasan  interpersonal anak, karena pembelajaran  reggio emilia merupakan  pembelajaran  melalui  metode proyek yang  secara tidak langsung  dapat  menstimulus anak  bekerja sama.